The Analysis Study of Early Detection and Outcome of Speech Delay in Children: A Comprehensive Systematic Review - Aldila, Raden Rara Farah; Erlich, Willyam Arnando Deggas (The International Journal of Medical Science and Health Research, 2024)
Background: Children of school age with language or speech delays are at a higher risk of encountering learning and literacy difficulties, particularly in reading and writing. This systematic review aims to evaluate the early detection and outcome of speech delay in children based on the literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Speech delay affects children's language and literacy, highlighting the need for early detection and intervention. Tailored diagnostic tools and understanding contributing factors are essential for implementing effective screening and targeted interventions to improve outcomes and foster positive developmental trajectories